2022
DOI: 10.1557/s43580-022-00321-3
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-dependent topology optimization of metallization grid patterns and variation of contact layer thickness used for latitude-based yield gain of thin-film solar modules

Abstract: We show that the concept of topology optimization for metallization grid patterns of thin-film solar devices can be applied to monolithically integrated solar cells. Different irradiation intensities favor different topological grid designs as well as a different thickness of the transparent conductive oxide (TCO) layer. For standard laboratory efficiency determination, an irradiation power of $$1000\,\mathrm {W/m}^2$$ 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…While a share of the PV community already agrees on the necessity to verify PV module performance under realistic operating conditions, the efficiency of CIGS solar cells as well as cell optimization approaches still refer to STC performance. Zinßer et al [11] showed that cell optimization w.r.t. STC can result in less yield compared with cell optimization w.r.t differing conditions based on typical meteorological year's irradiation data in different locations.…”
mentioning
confidence: 99%
“…While a share of the PV community already agrees on the necessity to verify PV module performance under realistic operating conditions, the efficiency of CIGS solar cells as well as cell optimization approaches still refer to STC performance. Zinßer et al [11] showed that cell optimization w.r.t. STC can result in less yield compared with cell optimization w.r.t differing conditions based on typical meteorological year's irradiation data in different locations.…”
mentioning
confidence: 99%